Military tactics and the rise of modern warfare, 1881-1935. (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2014)
This collection is drawn from the personal papers of Professor Henry Spensor Wilkinson (1853-1937) and traces the rise of modern warfare tactics through correspondence with some of Britain's most decorated military figures. Wilkinson's influential position as a military historian and journalist informed his correspondence with a range of military and political figures, including Prime Minister Herbert Asquith, Lord Kitchener, General Ian Hamilton, and Field Marshal William Robertson. As seen through the documents, Wilkinson discusses military strategy and events in the First World War, the Boer War in South Africa, as well as conflicts in the Balkans. The focal point of this collection covers the ascendency of modern warfare tactics, as nations transitioned from regular armies engaging in set piece battles, to the total warfare of World War One. As such, the collection offers a vital insight into how military tactics changed to reflect growing manpower and new technologies during the early 20th century.
Date range: 1881-1935.
Keywords: Tactics; Wilkinson, Spenser, -- 1853-1937 -- Correspondence